Technology-Assisted Attendance Monitoring: A Case Study on QR Code System Usability and Performance - Max Angelo Dapitilla Perin (Journal of Technology-Assisted Learning, 2025)
The increasing integration of digital technologies into academic administration has significantly improved operational efficiency, particularly in attendance monitoring. Traditional methods, such as manual sign-ins and biometric scanners, often have limitations, including time inefficiency, susceptibility to human error, and administrative burden. To address these issues, this study evaluated the usability and performance of the BISU-Bilar QR Code Generator and Contact Tracing System, which was repurposed for monitoring student attendance at Bohol Island State University–Bilar Campus. A mixed-methods research design was employed, combining quantitative data from structured surveys and qualitative insights from open-ended responses. The evaluation was guided by the ISO 25010 standard, focusing on key usability dimensions such as functional suitability, efficiency, reliability, and user satisfaction. Results from 106 respondents indicate that the system is generally functional, easy to learn, and effective in facilitating task completion. The highest-rated usability aspect was device compatibility, while system stability and security received the lowest scores, suggesting areas for technical improvement. Statistical analyses, including Principal Component Analysis (PCA) and Ordinary Least Squares (OLS) regression, revealed that system functionality and device compatibility significantly influence perceived efficiency. In contrast, system crashes and data security concerns negatively impact user experience. Visualized through a word cloud, qualitative feedback highlighted recurring themes such as the demand for real-time notifications, enhanced user interface design, and improved technical support. The study concludes that while the QR code-based system offers a practical and scalable solution for attendance tracking, targeted enhancements in system stability, cross-platform performance, and data protection are necessary to ensure reliability, boost user confidence, and promote long-term adoption within educational institutions.